Dupilumab Efficacy in Children with Palmoplantar Eczema - Nikolay N. Murashkin; Leonid A. Opryatin; Ekaterina S. Pavlova; Roman V. Epishev; Alexandr I. Materikin; Roman A. Ivanov; Mariya A. Leonova; Dmitriy V. Fedorov; Alena A. Savelova (Вопросы современной педиатрии)
Background. Atopic dermatitis (AD) is a chronic inflammatory skin disease with such clinical manifestations as eczematous lesions and itching. One of its clinical forms is palmoplantar eczema. It is urgent and unresolved issue in pediatric dermatology as this disease significantly affect the patients’ quality of life due to involvement of functionally significant areas, symptoms severity, difficult induction of remission. Clinical case description. This article presents case series of patients with AD involving palms and soles who have shown positive results to the treatment with genetically engineered biologic drug — dupilumab. Conclusion. Palmoplantar eczema, as one of the forms of AD, hardly responds to topical therapy in clinical practice of dermatologist. Moreover, systemic treatment is not only limited in pediatrics, but also is not effective enough. Prescription of the genetically engineered biologic drug, dupilumab, seems to be one of the effective methods for management of this disease in these patients.